Optical spectroscopy of young tidal objects around two interacting galaxy pairs - Lee-Waddell, K. (2018)
We present Gemini Multi-Object Spectrograph spectra of HI-rich tidal features located around the outskirts of two interacting galaxy pairs, NGC 3166/9 and NGC 4725/47. These follow-up observations are part of a multiwavelength campaign to study the properties and frequency of tidal dwarf galaxies (TDGs) in group environments. Based on the calculated gas-phase metallicity and redshift, in addition to the previously measured HI and stellar properties, we have confirmed the tidal origins of TDG candidate AGC 208457, which has emerged from the tidal debris of an interaction between the NGC 3166/9 galaxy pair. By comparing HI and optical recessional velocities, we have also confirmed a physical association of the gaseous knots and star clusters embedded in the metal-rich tidal tail of NGC 4747.